Mempermudah Pengawasan Operasional dan Keuangan di Biro Perjalanan dengan Menggunakan Aplikasi Gtass - Arifin, Furry (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Some travel agencies have difficulty in monitoring the operational control and generating financial report. This is due to the operation of the data storage for business transactions conducted separately , and the reporting of the financial statements company are still found not in accordance with the bank reconciliation . In this study, the methodology the system development life cycle (SDLC) is used ranging from data collection through interview, observation and study of the literature up to the stage of application development, namely the analysis phase in the travel agency using the method of direct observation of the flow through the reporting process. After that, go into the design stages of database design methods and user interface. Global Travel Agency System Solutions (GTASS) product is the integration system designed specifically for the corporate travel agency that exists to facilitate control operations, such as creating a bill (invoice), Letter of Gurantee (LG) and financial oversight as receipts and expenditure of money. With the ease of processing, then the presentation of the financial statements can be done automatically. Important early financial supervision carried out by the travel agency due to an increase in sales without adequate consideration of financial supervision, will lead to the emergence of new problems, which in turn will hamper efforts to increase the sales.